ORTIS FC - ORTIS FC (Tufts Archival Research Center, 2007)
Letter from Frank C. Curtis to James Savarese regarding his visit to the Aluminum Brick Glass Workers Union and his discussion with them about tobacco related issues. Discussed the Food and Drug Administration (FDA) regulations, clean indoor air and fair taxes as it relates to public employees.